Pemetaan Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A) Provinsi Sumatera Barat - Hallen Abu Bakar (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The Center of Integrated Service for Women and Children Empowerment (P2TP2A) is established by the government based community in order to eliminate the violence towards women and children. It also aims to empower the position of women and children. The purpose of the study is to describe comprehensively the existance of P2TP2A in sub-district, district, city, and province in West Sumatra. Descriptive qualitative research was used where the data taken from questionnaire and in-deepth-interview. The study found that the Center of Integrated Service for Women and Children Empowerment was established by following certain procedure, legality and personnel structure. It also found that the majority of P2TP2A in West Sumatra has insufficient infrastructures. Meanwhile, it is only P2TP2A Limpapeh Rumah Nan Gadang of West Sumatera, and P2TP2A Luhak Nan Tuo Batusangkar has sufficient infrastructures. Many of them were located at the corner of Community Empowerment and Women and Family Planning office (BPMPKB). Every P2TP2A in those district and city have made their programs, but they faced some difficulties in realize them doe to financial problems. The human resources were recruited from SKPD, academician, professional, society figures, LSM who concern on gender meanstreaming. They play the role more on providing the service than giving information and empowerment. The last finding of the study showed that the involvement of local government, Health offices, social services, police, ministry of religion, prosecutors and social services have been effective.